Margaret Atwood, Survival (1972): Topoi of Canadian Literature - Polić, Vanja (2004)
In this paper I propose to briefly list and discuss the key motifs that appear specifically in Canadian literature. As the title of Margaret Atwood's book suggests, the most frequent themes that appear in Canadian literature in English written by white immigrants are the perception of Nature (Nature as indifferent or hostile towards white immigrants) and animals ; the perception of "early people" and their understanding / representation of the divine (as opposed to the European understanding of the divine) ; the perception of women and of artists ; etc. The importance of these themes, according to Margaret Atwood, lies in the fact that these key patterns are typical for Canadian literature in English and thus distinguish it from other literatures.